Sarcopenic obesity: A new category of obesity in the elderly - Zamboni, Mauro; Mazzali, Gloria; Fantin, Francesco; Rossi, Andrea; Di Francesco, Vincenzo (Nutrition, metabolism, and cardiovascular diseases, 2008)
In elderly patients, age-related changes in body composition, as well as the increased prevalence of obesity, determine a combination of excess weight and reduced muscle mass or strength, recently defined as sarcopenic obesity (SO). This review examines the main studies regarding sarcopenic obesity in the elderly. Definition of SO necessarily combines those of sarcopenia and obesity. The prevalence of sarcopenia and SO increases with age. Muscle and fat mass are strongly interconnected from a pathogenetic point of view. A better understanding of the mechanisms which lead from loss of muscle mass to fat gain or vice versa from fat gain to muscle loss seems to be crucial. Recent data suggest that peptides produced by adipose tissue may play an important role in the pathophysiology of SO, thus more research is needed to better characterize this new area. Obesity and Sarcopenia in the elderly may potentiate each other maximizing their effects on disability, morbidity and mortality. Identifying elderly subjects with SO should be mandatory; effective treatment of sarcopenia and SO may attenuate its clinical impact. The concept of SO may help to clarify the relationship between obesity, morbidity and mortality in the elderly.